Surface energy budget and thermal inertia at Gale Crater: Calculations from ground‐based measurements. Issue 8 (8th August 2014) - Martínez, G. M.; Rennó, N.; Fischer, E.; Borlina, C. S.; Hallet, B.; de la Torre Juárez, M.; Vasavada, A. R.; Ramos, M.; Hamilton, V.; Gomez‐Elvira, J.; Haberle, R. M.
Abstract The analysis of the surface energy budget (SEB) yields insights into soil‐atmosphere interactions and local climates, while the analysis of the thermal inertia (I) of shallow subsurfaces provides context for evaluating geological features. Mars orbital data have been used to determine thermal inertias at horizontal scales of ~104 m2 to ~107 m2. Here we use measurements of ground temperature and atmospheric variables by Curiosity to calculate thermal inertias at Gale Crater at horizontal scales of ~102 m2. We analyze three sols representing distinct environmental conditions and soil properties, sol 82 at Rocknest (RCK), sol 112 at Point Lake (PL), and sol 139 at Yellowknife Bay (YKB). Our results indicate that the largest thermal inertia I = 452 J m−2 K−1 s−1/2 (SI units used throughout this article) is found at YKB followed by PL with I = 306 and RCK with I = 295. These values are consistent with the expected thermal inertias for the types of terrain imaged by Mastcam and with previous satellite estimations at Gale Crater. We also calculate the SEB using data from measurements by Curiosity's Rover Environmental Monitoring Station and dust opacity values derived from measurements by Mastcam. The knowledge of the SEB and thermal inertia has the potential to enhance our understanding of the climate, the geology, and the habitability of Mars.